Nilai-Nilai Pendidikan Tasawuf dalam Film “99 Kali Rindu” Karya Azhari Zain - Aldin, Fahri; Sahal, Yosep Farhan Dafik (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2020)
This study aims to (1) determine the meaning of Sufism education; (2) knowing the values ​​of Sufism education contained in the film